Rytm w perspektywach: lingwistycznej i neurobiologicznej - Młynarska, Grażyna (Investigationes Linguisticae, 2015)
This article is about rhythm from the linguistic and neurobiological perspectives. Comparing data from both domains could enable clarification of (long–term) confusion in acoustic and conceptual ideas of rhythm as well as providing a multidimensional definition of this category with solid neurobiological grounding and taking aspects of modeling speech production into consideration.